Resistance training practices of sprint coaches - Healy, R.; Kenny, I. C.; Harrison, A. J. (The Journal of Strength and Conditioning Research, 2021)
This study describes the results of a survey of resistance training practices of sprint coaches. This study investigated why sprint coaches prescribe resistance training to their athletes, what exercises they select, and what factors are involved with their selection. Forty-one of 73 (56%) sprint coaches with mean ± SD coaching experience of 8.4 ± 6.4 years were included in this study. Coaches completed an online questionnaire consisting of 5 sections: (a) informed consent, (b) coach background information, (c) coach education and qualifications, (d) coaches' views on resistance training, and (e) exercise selection and preference. The results showed that coaches prescribe resistance training to their sprint athletes to develop strength and power, which they believe will transfer to sprint performance. Coaches prescribed a wide variety of traditional, ballistic, and plyometric exercises, with the hurdle jump found to be the most widely prescribed exercise (93% of coaches surveyed). Coaches selected exercises for a variety of reasons; however, the 3 most prominent reasons were: (a) performance adaptations; (b) practicality; and (c) the targeting of muscles/muscle groups. Coaches prioritized exercises that specifically developed strength, power, and reactive strength for their sprint athletes. This research can be used to develop educational resources for sprint coaches who wish to use resistance training with their athletes. In addition, sprint coaches can use the data presented to expand their current exercise repertoire and resistance training practices.